Mercury biomagnification patterns in boreal and subarctic lake food webs - Piro, Alexander J.; Kozak, Natalia; Keva, Ossi; Eerola, Emmi S.; Kulo, Katja; Ruokonen, Timo J.; Weckström, Jan; Malinen, Tommi; Kiljunen, Mikko; Taipale, Sami J.; Kahilainen, Kimmo K. (Elsevier, 2025)
Climate change and land use are significant pressures on northern environments with the potential to influence mercury (Hg) biomagnification in lake food webs. How this process may differ along a north–south gradient, defined by simultaneously changing environmental characteristics, has not been thoroughly explored. Lake food webs, from primary producers to top predators, from 19 subarctic and 16 boreal lakes in Finland were tested for total Hg (THg) biomagnification through the linear regression of THg content (log10[THg]) and trophic level derived from δ15N. Climate, productivity, lake, and catchment variables were combined and assessed in a principal component analysis (PCA), and the first three principal components (PC) (71.1% of overall variability) were individually regressed with regional trophic magnification slopes (TMS), and mercury baselines ([THg] baseline). PC1 (climate–productivity), PC2 (water bodies), and PC3 (catchment metrics) were used in stepwise multiple linear regression models to assess the combined influence of PCs on regional TMS and [THg] baseline. Subarctic TMS and [THg] baseline were positively and negatively important, respectively, along a climate–productivity gradient (PC1). The stepwise model for subarctic TMS included PC1 and PC2, which explained 42.3% of variation, while the model for boreal TMS included all three PCs, which explained 35.4% of variation. The notable complexity of influences on boreal lakes makes modelling and future predictions challenging for this region, while the ongoing and simultaneous influences of climate warming and land use intensification in the subarctic region suggest lower TMS in the future.
Keywords: basal total mercury; food chain length; land use; stable isotopes; trophic magnification factor; trophic magnification slope